Biotransformation and Cytotoxic Activity of Guaiacol Dimer - Galuh Widiyarti; Jamilah Abbas; Yulia Anita (Indonesian Journal of Chemistry, 2014)
Guaiacol, a phenolic compound is known as an anticancer. Dimerization of guaiacol has been done by biotransformation using peroxidase enzyme as biocatalyst. This enzyme was isolated from Indonesian plant, kailan (Brassica oleraceae var. alboglabra). Analysis of dimerization product was carried out by TLC, IR, LC-MS, and NMR. Whilst analysis of in-vitro cytotoxic activity was carried out by MTT method against breast cancer T47D and MCF7 cells. The result showed that the dimerization reaction gave O-para dehydroguaiacol. The in-vitro cytotoxic activity analysis showed that O-para dehydroguaiacol compound has potency as anti-breast cancer.